Transition or Tradition: Imagining National R&D Innovation in South Korea - Shin, Youjung; Jeong, Hanbyul (NOvation — Critical Studies of Innovation, 2019)
From the late 1990s, many national policies for research and development (R&D), focusing on innovation, were established in South Korea. In May 2015, the Korean government announced another bold blueprint for R&D innovation emphasizing a serious approach toward overcoming outdated ideas and practices regarding the governance of the science and technology sectors. This emphasized very high expectations for the country, though in the end it brought brutal criticism and bitter disappointment. This paper conducts a critical analysis of the discourse surrounding the notion of national R&D innovation by focusing on the case of the 2015 Government R&D Innovation Plan. Various (un)published papers were examined as mediators to reproduce, construct, and deliver a particular imagination. By analyzing not only the final policy documents but also the initial policy draft, this paper highlights a substantive discontinuity in the formation of the 2015 Government R&D Innovation Plan that illuminates different imaginations of so-called national innovation in terms of R&D. It illustrates a tension occurring in national R&D innovation in South Korea between the desire to reproduce past glory by following previous experiences and a willingness to embody semantic meanings of innovation with novel approaches. This paper reveals a discursive oscillation of imaginations in national R&D innovation which resulted in its conceptual and practical ambiguity.